Pet and Stray Dogs as Reservoirs of Antimicrobial-Resistant Escherichia coli - Laura Marchetti; Daniel Buldain; Lihuel Gortari Castillo; Andrea Buchamer; Manuel Chirino‐Trejo; Nora Mestorino (International Journal of Microbiology, 2021)
The close contact between dogs and humans creates the best bridge for interspecies transmission of antimicrobial-resistant bacteria. The surveillance of its resistance including the detection of extended-spectrum beta-lactamases (ESBLs) in Escherichia coli as indicator bacteria is an important tool to control the use of antimicrobials. The aim of this research was to evaluate the E. coli resistance in strains by phenotypic methods, isolated from pet and stray dogs of La Plata city, Argentina. Faecal samples were collected using rectal swabs from 50 dogs with owners (home dogs = HD) and 50 homeless dogs (stray dogs = SD). They were cultured in 3 MacConkey agar plates, with and without antibiotics (ciprofloxacin and cefotaxime). 197 strains were isolated, of which only 95 strains were biochemically identified as E. coli, 46 strains were from HD, and 49 were from SD. Antimicrobial susceptibility was evaluated by the Kirby–Bauer disk diffusion method. The most prevalent resistance was for tetracycline, streptomycin, and ampicillin. In both groups, the level of resistance to 3rd generation cephalosporins was high, and there were multiresistant strains. There was a higher level of antimicrobial resistance in strains from SD compared to HD. There were 8% of strains suspected of being ESBLs among samples of HD and 36% of SD. One (2%) of the strains isolated from HD and 11 (22%) from SD were phenotypically confirmed as ESBL. Pets and stray dogs are a potential source of E. coli antibiotic resistance in Argentina; therefore, its surveillance must be guaranteed.